New frontiers of temporary buildings. Passive housing modules - Federica Ribera; Rossella Del Regno; Pasquale Cucco (Agathón)
The purpose of this paper is to examine the characteristics of temporary buildings created to flexibly respond to the needs and necessities of people involved in natural disasters or in hardship cases. Architecture technology allows an industrialized modular low-cost building system, in case of an emergency – the ease and speed of the assembling process, flexibility, and immediate use – and the conditions of temporality: to create a light, removable, transportable, transformable, reusable and, at the same time, durable and adaptable to the territory’s climate and morphology building. It is a design proposal characterized by the use of passive systems which, by incorporating local resources, and recycled or recyclable materials, can guarantee the sustainability of the entire production process aiming to provide an efficient, quick and low-cost response, without neglecting architectural aspects, housing comfort and environmental impact.